EDI/XML in e-commerce - Bryndís Sigurðardóttir (2004)
Verkefnið er opið nemendum og starfsfólki Háskólans á Akureyri This dissertation handles EDI and XML in the Internet environment. It handles what kinds of companies are today using EDI and which companies are not. This dissertation describes possible solutions for companies not using EDI and states one that is chosen to solve this problem. There is no technology used in Iceland today as far as I know that handles this problem. There are groups and companies researching the use of EDI and XML together, for example Icepro. Good explanations are in the dissertation of all the technical terms used when solving this problem. There are more detailed explanations on EDI then other techniques because EDI is not a term used in the computer science environment as much as for instance XML and XSLT. Some discussion is about related work and numbers of systems are mentioned. These systems are used to compare to the solution created in this project.